2015
DOI: 10.1093/jme/tjv140
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Pathogenic Filamentous Fungi and Yeasts From Adult House Fly (Diptera: Muscidae) Captured From the Hospital Environments in Ahvaz City, Southwestern Iran: Table 1.

Abstract: Musca domestica L., 1758 is capable of transferring a number of pathogenic viruses, bacteria, fungi, and parasites to animals and humans. The objective of this study was to isolate and identify medically important filamentous fungi and yeasts from adult M. domestica collected from two wards of three hospital environments in Ahvaz city, Khuzestan Province, southwestern Iran. The common house flies were caught by a sterile net. These insects were washed in a solution of 1% sodium hypochlorite for 3 min and twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…(1, 2, 6)240.18 Alternaria alternata Fries (4)110.05 Epicoccum nigrum Link (3)1582.62Fungal sinusitis in the southeastern US (Noble et al 1997) Leptosphaerulina sp.110.05 Phaeosphaeria sp.110.05 Saccharomycetales Candida panamensis Suh et al110.05Beetle-associated (Suh et al 2006) Kluyveromyces marxianus Hansen3210.95Cow and goat milk (Delavenne et al 2011) Pichia jadinii Sartory et al1281.26 Pichia kudriavzevii Boidin et al110.05Bovine mastitis, Dairy cattle rumenal fluid (Hayashi et al 2013, Sirisan et al 2013) Xylaniales Hansfordia sinuosae Li & Cheng1140.63a

Fungi previously reported in the literature are noted. 1 Davari et al (2012), 2 Kassiri et al (2015), 3 Phoku et al (2016), 4 Sales et al (2002), 5 Srivoramas et al (2012), 6 Yousef (2014), 7 Zarrin et al (2007).

bTotal number of flies from which particular fungal isolates were recovered.cNumber of colony-forming units (CFU).dReferen...
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(1, 2, 6)240.18 Alternaria alternata Fries (4)110.05 Epicoccum nigrum Link (3)1582.62Fungal sinusitis in the southeastern US (Noble et al 1997) Leptosphaerulina sp.110.05 Phaeosphaeria sp.110.05 Saccharomycetales Candida panamensis Suh et al110.05Beetle-associated (Suh et al 2006) Kluyveromyces marxianus Hansen3210.95Cow and goat milk (Delavenne et al 2011) Pichia jadinii Sartory et al1281.26 Pichia kudriavzevii Boidin et al110.05Bovine mastitis, Dairy cattle rumenal fluid (Hayashi et al 2013, Sirisan et al 2013) Xylaniales Hansfordia sinuosae Li & Cheng1140.63a

Fungi previously reported in the literature are noted. 1 Davari et al (2012), 2 Kassiri et al (2015), 3 Phoku et al (2016), 4 Sales et al (2002), 5 Srivoramas et al (2012), 6 Yousef (2014), 7 Zarrin et al (2007).

bTotal number of flies from which particular fungal isolates were recovered.cNumber of colony-forming units (CFU).dReferen...
…”
Section: Resultsmentioning
confidence: 99%
“…1 Davari et al (2012), 2 Kassiri et al (2015), 3 Phoku et al (2016), 4 Sales et al (2002), 5 Srivoramas et al (2012), 6 Yousef (2014), 7 Zarrin et al (2007).bTotal number of flies from which particular fungal isolates were recovered.cNumber of colony-forming units (CFU).dReferences to importance of fungal isolates as disease agents or allergens.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…28, Wang et al, 2017) might also prove useful. A specific case, in point, is the study of Kassiri et al (2015) where they examined adult house flies from hospitals in Iran and showed 80% of the flies carried one or more species of medically important fungi. They did not, however, explore where these pathogens were located within the flies.…”
Section: The Crop As a Site For Biofilm Formation And Microbial Prolimentioning
confidence: 99%